Opportunities and challenges of World System in Nepal (The Journal of Sindhuli Multiple Campus, 2026)
In the present global context, three types of economies are seen to exist: capitalist economy, socialist economy, and mixed economy. The countries that have adopted each of these economic systems have established international relations according to their own historical, economic, political, and social contexts. Such international relations appear favorable to powerful nations, while weaker nations are often compelled to remain in a dependent position. In this way, the current world system is functioning. On the basis of this world system, interdependence among nations has been established, and accordingly, they are compelled to face both opportunities and challenges.